Protective Effects of Dendropanax morbifera against Cisplatin-Induced Nephrotoxicity without Altering Chemotherapeutic Efficacy - Ji Su Kim; Kyeong Seok Kim; Ji Yeon Son; Hae Ri Kim; Jae Hyeon Park; Su Hyun Lee; Da Eun Lee; In Su Kim; Kwang Youl Lee; Byung Mu Lee; Jong Hwan Kwak; Hyung Sik Kim (MDPI AG, 2019)
Use of the chemotherapeutic agent cisplatin (CDDP) in cancer patients is limited by the occurrence of acute kidney injury (AKI); however, no protective therapy is available. We aimed to investigate the renoprotective effects of Dendropanax morbifera water extract (DM) on CDDP-induced AKI. Male Sprague-Dawley rats (six animals/group) received: Vehicle (control); CDDP (6 mg/kg, intraperitoneally (i.p.); DM (25 mg/kg, oral); or DM + CDDP injection. CDDP treatment significantly increased blood urea nitrogen (BUN), serum creatinine (sCr), and pro-inflammatory cytokines (IL-6 and TNF-α), and severely damaged the kidney architecture. Urinary excretion of protein-based AKI biomarkers also increased in the CDDP-treated group. In contrast, DM ameliorated CDDP-induced AKI biomarkers. It markedly protected against CDDP-induced oxidative stress by increasing the activity of endogenous antioxidants and reducing the levels of pro-inflammatory cytokines (IL-6 and TNF-α). The protective effect of DM in the proximal tubules was evident upon histopathological examination. In a tumor xenograft model, administration of DM enhanced the chemotherapeutic activity of CDDP and exhibited renoprotective effects against CDDP-induced nephrotoxicity without altering chemotherapeutic efficacy. Our data demonstrate that DM may be an adjuvant therapy with CDDP in solid tumor patients to preserve renal function.